Personal performance techniques - Luft, Greg; First Light Video Publishing; TMW Media Group Inc. (Venice, CA. : First Light Video Publishing : TMW Media Group Inc. [distributor], 2003)
Outlining a practical five-step method, this program teaches viewers how to deliver clear and compelling presentations. It explains how to effectively use visual cues, shows performance techniques, and discusses how personal appearance can sway an audience
Title from title screen
Keywords: Public speaking; Self-presentation